63. Geology and Ore Deposits of the Questa Molybdenum Mine Area, Taox County, New Mexico - Robert H. Carpenter (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Molybdenite mineralization occurs in the hood zone of the Questa mine aplite-porphyry intrusive, one of the three sil ica-rich intrusive5 occurring along the east-west trending Red River Trench that crosses the northerly trending Sangre de Cristo Mountains in north-central New Mexico. The Trench is located immediately north of the circular Gold Hill positive block between the Red River and Cabresto Creek drainages. The aplite-porphyry bodies intruded a mid-Tertiary volcanic section consisting of lower andesites, overlain by latites and rhyolites. They occur largely in the andesites and were emplaced mainly by metasomatism rather than by sloping. Hydrothermal alteration occurs both as blanket propylitization in the volcanics and sericitization and kaolinization in the porphyries and as halo-type alteration outward from veins and shear zones resulting in strong biotization in the volcanics and sericitization and kaolinization in the aplitic rocks. Mineralization consists of: ( 1) molybdenite- quartz veinlets; (2) banded molybdenite, quartz veins frequently with biotite and potash feldspar along the walls and occasionally with minor lead, zinc, and copper sulfides and with fluorite and carbonates when again reopened; ( 3) high grade molybdenite locally along shear zones; and ( 4) molybdenite paint along joint and fracture surfaces. The mineralization was associated with faulting that resulted from numerous periods of gravity adjustment along the Trench and was controlled by the major shear systems that trend northeast, east-west and north-south to northwest. Molybdenite has been well oxidized in nearsurface exposures to ferrimolybdite and the molybdenum-bearing ferric hydroxide, akaganeite. The oxidation of the abundant pyrite within the veins and shear zones and of the alteration pyrite in the volcanics resulted in a low pH environment under which the acid molybdate ion released by oxidation was fixed either in the ferrimolybdite or the akaganeite molecule in the veins and shear zones or in the soils. Little has been lost in the runoff.